PENGELOLAAN KRISIS INFORMASI DAN MEDIA DI HUMAS SEKRETARIAT DPRD KOTA MEDAN - Rahmah, Alvia; Nasution, Annio Indah Lestari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Information crisis is an inevitable challenge in the context of local government such as Medan City Council. In an era of rapidly connected globalization, the ability to manage information crises is crucial to maintaining public trust and government stability. The public relations of the Medan City DPRD Secretariat plays an important role in handling the information crisis, with transparency and trust as key elements in building a strong relationship between the government and the community. This study used a qualitative approach with data collection techniques such as in-depth interviews, document analysis, and direct observation. Data analysis highlighted key challenges faced by PR, such as message control, speed of response, and internal coordination. Nonetheless, the communication strategies implemented by the PR proved effective, including transparency, message consistency, and the use of diverse communication channels. Quick and effective responses to critical situations, driven by public trust, were key in managing the information crisis. In conclusion, it is important for Medan City Council to continuously improve transparency in the delivery of information to the public and build strong trust by responsively responding to critical situations that arise. By doing so, they can ensure effective information crisis management, maintain government stability, and strengthen the positive relationship between the government and the people in Medan City.